Branch-Chain-Rich Diisopropyl Ether with Steric Hindrance Facilitates Stable Cycling of Lithium Batteries at − 20 °C - Li, Houzhen; Kang, Yongchao; Wei, Wangran; Yan, Chuncheng; Ma, Xinrui; Chen, Hao; Sang, Yuanhua; Liu, Hong; Wang, Shuhua (Nano-Micro Letters, 2024)
Li metal batteries (LMBs) offer significant potential as high energy density alternatives; nevertheless, their performance is hindered by the slow desolvation process of electrolytes, particularly at low temperatures (LT), leading to low coulombic efficiency and limited cycle stability. Thus, it is essential to optimize the solvation structure thereby achieving a rapid desolvation process in LMBs at LT. Herein, we introduce branch chain-rich diisopropyl ether (DIPE) into a 2.5 M Li bis(fluorosulfonyl)imide dipropyl ether (DPE) electrolyte as a co-solvent for high-performance LMBs at − 20 °C. The incorporation of DIPE not only enhances the disorder within the electrolyte, but also induces a steric hindrance effect form DIPE’s branch chain, excluding other solvent molecules from Li+ solvation sheath. Both of these factors contribute to the weak interactions between Li+ and solvent molecules, effectively reducing the desolvation energy of the electrolyte. Consequently, Li (50 μm)||LFP (mass loading 10 mg cm−2) cells in DPE/DIPE based electrolyte demonstrate stable performance over 650 cycles at − 20 °C, delivering 87.2 mAh g−1, and over 255 cycles at 25 °C with 124.8 mAh g−1. DIPE broadens the electrolyte design from molecular structure considerations, offering a promising avenue for highly stable LMBs at LT. Highlights: 1 Branch chain-rich diisopropyl ether (DIPE) was selected as co-solvent of low-temperature electrolyte for lithium metal battery. 2 The introduction of DIPE improved the disorder of electrolyte and the branch chains from DIPE exclude other solvents from the Li+ solvent sheath, thereby achieving a rapid desolvation process. 3 The electrolyte guaranteed a uniform Li stripping and deposition during cycling at both room temperature and low temperature and ensured stable cycling performance for Li||LFP cells over 650 cycles at − 20 °C.